2016
DOI: 10.1039/c5qo00439j
|View full text |Cite
|
Sign up to set email alerts
|

Au/TiO2catalyzed reductive amination of aldehydes and ketones using formic acid as reductant

Abstract: The combination of commercial easily available Au/TiO2 as catalyst and cost-effective formic acid as reductant was able to render reductive amination of various carbonyl compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 77 publications
1
36
0
Order By: Relevance
“…[9] Compared with other methods, reductive aminationh as several advantages such as good availability of the substrates and high atomic efficiency.T he reductivea minationo fc arbonyl compounds with primary amines has been extensively studied for the synthesis of secondary amines. [10][11][12] Primary amines can be simply produced by the hydrogenation of nitro compounds prior to use. Thus, it is attractive to perform ao ne-potr eductive aminationo fc arbonyl compounds with nitro compounds for the synthesis of secondary amines,w hich avoidst he separation and purification of the primary amines in the first step.…”
mentioning
confidence: 99%
“…[9] Compared with other methods, reductive aminationh as several advantages such as good availability of the substrates and high atomic efficiency.T he reductivea minationo fc arbonyl compounds with primary amines has been extensively studied for the synthesis of secondary amines. [10][11][12] Primary amines can be simply produced by the hydrogenation of nitro compounds prior to use. Thus, it is attractive to perform ao ne-potr eductive aminationo fc arbonyl compounds with nitro compounds for the synthesis of secondary amines,w hich avoidst he separation and purification of the primary amines in the first step.…”
mentioning
confidence: 99%
“…Terminal aliphatic alkyne also worked well ( Table 5, entry 5). The hydration of internal alkynes was slower than that of terminal alkynes, and a slightly higher catalyst loading (1 mol %) was needed to achieve good yields ( Table 5, entries [6][7][8]. Alkenes and carboxylic acids were well tolerated ( Table 5, entries 9 and 11), but the -OH group in 1-ethynylcyclohexanol (2'-1j) did not survive the hydration condition ( Table 5, entry 10).…”
Section: Substrates Scope and Discussionmentioning
confidence: 99%
“…Primary amines (Table 17, entries 1-5), cyclic secondary amines (Table 17, entries [6][7][8] and acyclic secondary amines ( It was also found that when the amine partners were absent, the tandem reduction/formylation product 6-6 could be obtained in one pot. Because deformylation could be achieved selectively in the presence of other ester groups, this O-formylation method may prove beneficial on those reactions that need to protect alcohol groups in a complex synthetic sequence.…”
Section: Substrates Scopes and Discussionmentioning
confidence: 99%
See 2 more Smart Citations